The Sleeping Giant Who Left for America: The Determinants and Impact of Danish Emigration During the Age of Mass Migration - Nina Boberg-Fazlić; Markus Lampe; Paul Sharp (European Historical Economics Society (EHES), 2021)
What determines emigration, and what impact does it have on the sending country? We consider the case of Denmark between 1868 and 1908, when a large number of people left for America. A significant fraction of these were tyender, a servant-like occupational group that was heavily discriminated against at the time, and who saw little opportunities for advancement at home. We exploit the fact that the Danish agrarian reforms between 1784 and 1807 had differential impacts on this class of landless laborers around the country, and use detailed parish-level data – police protocols of emigrants; population censuses and land registers – to show that areas with a more unequal distribution of land witnessed larger emigration. We then use income tax data, finding evidence of a positive income effect on the areas which saw most emigration.
Keywords: J15; N33; O15; 330; Agrarian reform; Denmark; emigration; landless laborers